Pengaruh Latihan Speed Agility dan Ball Feeling Terhadap Kemampuan Teknik Dribbling Futsal Siswa MAN 2 Bone - Andi Muh Sulihin; Andi Mutmainna; Rahmat Ilahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of speed agility and ball feeling training on dribbling technique ability in futsal among students of MAN 2 Bone. The study employed a quantitative approach using an experimental method with a one-group pretest–posttest design. The research sample consisted of 16 students participating in the futsal extracurricular program at MAN 2 Bone, selected using a total sampling technique. The research instrument was a futsal dribbling test. Data were analyzed using descriptive statistics and hypothesis testing. The results showed that speed agility and ball feeling training had a significant effect on improving students’ futsal dribbling technique. Therefore, both training methods are effective alternatives for training programs to enhance basic futsal dribbling skills.